Penguatan branding dan digital engagement pada UMKM Cafe D’Boss di Kabupaten Sampang - Karisa Juwita Permata Sari; Roihan Amin; Ach. Wahyudi; Abdul Manaf; Oyong Fardatullah Galuh S; Savina Ainung Nasiha; Ayu Sri Agustini; Mahreza Reco Alvian Akbar; Oktavian Tri Fujianto; Moh. Indra Bintang Maulana; Fadali Rahman (Penamas: Journal of Community Service, 2026)
The development of culinary micro, small, and medium enterprises in rural areas frequently faced challenges, including limited geographic reach, weak brand identity reinforcement, and minimal digital engagement. Cafe D’Boss experienced these problems in Sampang Regency, which still relied on conventional marketing, thereby limiting its market reach. This community service activity aimed to increase digital marketing capacity by reinforcing brand identity and fostering online consumer engagement. The implementation method utilized a qualitative participatory approach encompassing observation, interviews, education, practical mentoring, and evaluation. Implemented solutions included migrating business communication to business-based messaging applications to increase transaction efficiency and preparing short-form video content planning documents tailored to current social media trends. The results demonstrated increased understanding, skills, and commitment of the entrepreneur in utilizing digital technology. The activity concluded that the synergy between local service quality and digital marketing strategies successfully expanded market reach to the regency level.